Antiaging Cream Formula From Lemongrass Leaf Extract (Chymbopogon Citratus) - Ramadhani, Shafira; Nyoman Ehrich Lister, I; Fachrial, Edy; Hakim Nasution, Ikhwanul (International Journal of Health and Pharmaceutical (IJHP), 2023)
This study aimed to determine the formula of anti-aging cream using lemongrass leaf extract. The treatment by giving respondents lemongrass leaf extract and using moisture, evenness, pore, spot, and wrinkle as parameters. Human skin provides protection on the surface of the body against the influence of the surrounding environment. Skin can experience aging, especially in areas that are often exposed to direct sunlight such as the face, neck, upper arms, and hands. Aging is a process experienced by humans in their 30s whose functions in the human body are decreasing, for example, thinning skin, wrinkles, rough skin, and dark spots on the face. Treatment to prevent aging of the skin by using an antioxidant product such as flavonoids because it has the function of preventing or neutralizing free radicals. In Indonesia, several species of plants can be found that function as food and cosmetic ingredients. The lemongrass leaf extract which contains antiaging are Alkaloids, Flavonoids, and Tannins. The data were analysed by using the Kolmogorov-Smirnov method to determine homogeneity and normality. Then, if the data is normal, it is continued to be analysed using the One-Way ANOVA method to determine the average difference between groups. There is a difference between treatments, and it is continued with the Post-hoc Tukey HSD test. The higher the concentration of extract used, the greater the anti-aging productivity formed. It is concluded, the best anti-aging effect is a concentration of 9% with increase in moisture, evenness, pore reduction, reducing spots and wrinkles.